Pendidikan usia prabaligh dalam surat An-Nuur ayat 31 dan 58 dalam tinjauan tafsir dan sains - Jatiningsih, Euis Sufi; Rahman, Imas Kania; Tanjung, Hendri (TAWAZUN: Jurnal Pendidikan Islam, 2024)
It is quite disturbing to see the moral state of teenagers today. Poor religious maturity is demonstrated by deviations in sexual behaviour, crime, and morality. Therefore, it is crucial to focus on education while a child is a pre-teen. This essay analyses Surah An-Nuur verses 31 and 58 in relation to the pre-baligh age's educational component. The research is being done in order to give us, as parents and Muslim communities, a solid and fundamental understanding of how to carry out the education process for kids in the pre-baligh age range. The approach employed in this study is library research with primary data drawn from Surah An-Nuur verses 31 and 58 as well as their numerous book-based interpretations, and secondary data drawn from many related books and articles. From this research it can be formulated that pre-baligh age education needs to pay attention to the following things: 1) Children pre balighaged must be kept safe so that they do not see their private parts 2) Children aged pre baligh be taught the etiquette of entering other people's rooms 3) Children pr baligh aged must know how to be ready for mahrom and know the limits of their private parts 4) Children aged before puberty must be kept away from watching or displaying pornography, because it will damage the brain and will further damage one's achievements and morals. Abstrak Melihat kondisi moral anak-anak remaja akhir-akhir ini sangat mengkhawatirkan. Penyimpangan perilaku seksual kejahatan dan buruknya akhlak menunjukkan kematangan religiusitas yang kurang baik. Maka sangat penting diperhatikan Pendidikan di usia prabaligh. Tulisan ini mengupas sisi Pendidikan usia prabaligh dari surat an Nuur ayat 31 dan 58. Tujuan dari penelitian yang diakukan adalah agar kita, para orangtua dan masyarakat muslim memiliki pemahaman yang kuat dan mendasar dalam melakukan proses Pendidikan terhadap anak di usia prabaligh. Metode yang digunakan dalam penelitian ini adalah library research dengan data primer yaitu kitab tafsir dari surat An Nuur ayat 31 dan 58 beserta dari berbagai kitab, sebagai data sekunder digunakan berbagai buku dan artikel terkait. Dari penelitian ini ditemukan bahwa Alquran sangat selaras dengan sains dalam menjelaskan Pendidikan usia prabaligh. Bahwa dalam pendidikan prabaligh perlu diperhatikan beberapa hal yaitu: 1) Anak usia prabaligh harus dijaga agar tidak melihat aurat 2) Anak usia prabaligh harus diajari adab memasuki kamar orang lain 3) Anak usia prabaligh harus mengetahui siapa saja mahrom dan mengetahui batasan auratnya 4) Anak usia prabaligh harus dijauhkan dari tontonan atau tayangan pornografi, karena akan merusak otak dan selanjutnya akan merusak prestasi dan akhlaknya.